2017
DOI: 10.1111/pan.13174
|View full text |Cite
|
Sign up to set email alerts
|

Using quality improvement methods to reduce clear fluid fasting times in children on a preoperative ward

Abstract: By using established QI methodology we reduced the mean fluid fasting time for day admissions at our hospital to 3.1 hours and increased the proportion of children fasting for less than 4 hours from 19% to 72%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 26 publications
2
123
2
4
Order By: Relevance
“…Herein, fasting durations were much longer than that recommended in current guidelines that allow clear fluids up to 2 hours and milk and light meal up to 6 hours prior to the surgery . This may constitute a limitation of this study, especially since some authors and several societies of pediatric anesthesiologists currently suggest even shorter fasting durations in the setting of pediatric anesthesia . In clinical practice, fasting durations are generally much longer than that recommended, in both adults and children .…”
Section: Discussionmentioning
confidence: 93%
“…Herein, fasting durations were much longer than that recommended in current guidelines that allow clear fluids up to 2 hours and milk and light meal up to 6 hours prior to the surgery . This may constitute a limitation of this study, especially since some authors and several societies of pediatric anesthesiologists currently suggest even shorter fasting durations in the setting of pediatric anesthesia . In clinical practice, fasting durations are generally much longer than that recommended, in both adults and children .…”
Section: Discussionmentioning
confidence: 93%
“…Andersson et al showed that dispensing with the 2 hours fasting limit for clear fluids was not associated with an increased incidence of pulmonary aspiration, and other studies found that the stomach processes a light meal in less than 4 hours . For a better implementation of improved fasting regimens, Newton et al favored a structured quality improvement program leading to an increased proportion of children fasting less than 4 hours after the introduction of a standard operating procedure checking the fasting status on admission and allowing clear fluids up to 1 hour before anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Shortened fasting times may improve the metabolic and hemodynamic condition during induction of anesthesia and the perioperative experience for parents and children with a low risk of aspiration and simplify perioperative management. As a consequence, some centers have reduced the fasting requirements for clear fluids to 1 hour and for light meals to 4 hours . In a recent review, Frykholm et al suggested that this change should be done ideally within a framework of a large multicenter audit monitoring the benefits and safety of the more liberal fasting regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Children undergoing an elective procedure under general anesthesia are required to fast to avoid the presence of solid gastric contents and lower the risks of regurgitation and pulmonary aspiration. A prolonged fasting time for clear fluids can have adverse effects, such as hunger, discomfort, headache, dehydration, hypovolemia, and hypoglycemia, and as a result, some pediatric hospitals have engaged in projects to reduce their preoperative fasting times for clear liquids . Dehydration and hypovolemia can increase the difficulty of establishing vascular access, though this association has not been clearly established in the literature.…”
Section: Introductionmentioning
confidence: 99%